VARIANTS OF THE COURSE OF CHRONIC PYELONEPHRITIS. MEDICAL AND SOCIAL EXAMINATION, REHABILITATION - Narzilloeva Z. Zh. (Web of Journals Publishing, 2024)
Pyelonephritis is a non-specific infectious inflammatory disease of the kidneys that affects the renal parenchyma (mainly interstitial tissue), pelvis and calyces.
Keywords: Tubulointerstitium , prostaglandins , Escherichia coli, renal pelvis.